ANALISIS PENGARUH KUALITAS PELAYANAN DAN KESESUAIAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Nugraha, Irsa Maulian; Y Sugiarto, Y Sugiarto (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effect arising from the quality of service, price Conformity, to customer satisfaction and its impact on consumer repurchasing decisions Depo Grocery Store. Variables used in this research is the quality of service and price suitability as an independent variable, and customer satisfaction as an intervening variable, and the repurchase decision as the dependent variable.This research method using purposive sampling with a sample of 157 respondents in the consumer Depo Sembako. The analytical method used in this research is quantitative analysis and analysis using analysis kualitatf Structural Equation Model (SEM) operated by AMOS program version 20.0. This type of data is primary data and using a questionnaire with open questions closed.The results of this study prove all hypothesis is accepted. 5 accepted hypothesis includes the positive effect of service quality on customer satisfaction, compliance rates positive effect on customer satisfaction, customer satisfaction has positive influence on the repurchase decision, service quality has positive influence on the repurchasing decisions and price suitability positive influence on the repurchase decision.